2011
DOI: 10.1371/journal.pone.0020470
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokine Profiles in Subjects with High-Functioning Autism Spectrum Disorders

Abstract: BackgroundAccumulating evidence suggests that dysregulation of the immune system is involved in the pathophysiology of autism spectrum disorders (ASD). The aim of the study was to explore immunological markers in peripheral plasma samples from non-medicated subjects with high-functioning ASD.Methodology/Principal FindingsA multiplex assay for cytokines and chemokines was applied to plasma samples from male subjects with high-functioning ASD (n = 28) and matched controls (n = 28). Among a total of 48 analytes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
163
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(178 citation statements)
references
References 36 publications
14
163
1
Order By: Relevance
“…Th17 cells and their cytokine mediators have been suggested to have a role in ASD. Increased levels of IL-17 have been found in blood from subjects with ASD [19,39,40]. In the maternal immune activation (MIA) mouse model of ASD, systemic blockage of IL-17 inhibited the MIA-induced ASD-like behavior in the offspring, suggesting that IL-17 plays an important role during the pathophysiological process of ASD [41].…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells and their cytokine mediators have been suggested to have a role in ASD. Increased levels of IL-17 have been found in blood from subjects with ASD [19,39,40]. In the maternal immune activation (MIA) mouse model of ASD, systemic blockage of IL-17 inhibited the MIA-induced ASD-like behavior in the offspring, suggesting that IL-17 plays an important role during the pathophysiological process of ASD [41].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Earlier studies have documented prominent microglial activation and increased production of inflammatory cytokines and chemokines, including interferon gamma (IFN-g), interleukin (IL)-1b, IL-6, IL-12p40, tumor necrosis factor alpha (TNF-a), and chemokine (C-C motif) ligand 2 (CCL2) in the brain tissue and cerebrospinal fluid (CSF) of some individuals with ASD. 3,7 Although findings are not consistent, there is growing evidence indicating elevated plasma levels of pro-inflammatory cytokines, including TNF-a, IFN-g, IL-1b, IL-6, IL-12, IL-17A, IL-23, [8][9][10][11][12][13][14][15] and decreased plasma levels of the anti-inflammatory cytokines IL-10 and transforming growth factor-beta (TGF-b) in children with ASD as compared to controls. 1,16 Although the phenotypic and neurobiological heterogeneity in ASD might be underlying factors that account for inconsistent findings, it should also be noted that important confounding factors influencing immune markers, such as medication and body mass index (BMI), have not been adequately addressed in previous research.…”
Section: Introductionmentioning
confidence: 99%
“…Another cytokine that seems to be implicated in ASD is TGF-β 1 , which is decreased in plasma levels of children with autism when compared with typically developing controls [6]. Interestingly, a recent study investigating several immune mediators found an increase of IL-17 in autistic patients, suggesting that Th17 response may be also involved in ASD [7]. Even though all these papers have shown changes in immune parameters in ASD, it is not clear whether the immune system is involved in the onset of ASD.…”
Section: Introductionmentioning
confidence: 99%